The effect of delivery type on uncoupling protein-2 levels. (16th September 2016) - Aslan, Yakup; Kader, Şebnem; Mutlu, Mehmet; Sarıaydın, Mehmet; Aran, Turhan; Alver, Ahmet; Kahraman, Cemil
Abstract: Objective : Uncoupling proteins (UCPs) are carrier proteins located in the mitochondrial inner membrane that disturb the proton gradient by re-transporting protons and that thus inhibit ATP synthesis. UCP-2 is found in in several tissues, particularly the brain. This study was performed to examine the effects of mode of delivery on UCP-2 in humans. Methods : The study was performed prospectively. Cord blood specimens were collected for measurement of blood gasses, full-blood count, total and direct bilirubin levels and UCP-2. UCP-2 levels were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Results were expressed as nanogram per milliliter. Results : The study was performed with 120 healthy term babies, 60 born by normal spontaneous vaginal delivery (NSVD) and 60 by cesarean/section (C/S). There was significant difference in UCP-2 levels between the two groups. UCP-2 levels were significantly higher in the cases born by NSVD then in the cases born by C/S. Conclusion : This study showed that a correlation exists between mode of delivery and UCP-2 in humans. As UCP-2 is described as playing a significant role in the formation of nerve cells and deficiency of this protein during development of the brain may lead to behavioral problems extending to adulthood, we think that increasing UCP-2 levels through normal delivery will protect all organs, and particularly the brain, against oxidative damage and play a role in preventing organ dysfunctions.